Effect of hydrogen direct injection strategies and ignition timing on hydrogen diffusion, energy distributions and NOx emissions from an opposed rotary piston engine. (15th December 2021) - Gao, Jianbing; Wang, Xiaochen; Tian, Guohong; Song, Panpan; Ma, Chaochen; Huang, Liyong
Graphical abstract: Highlights: Opposed rotary piston engines deliver high power density. Hydrogen direct injection applications to this novel engine are explored. In-cylinder combustion and thermal efficiency are insensitive to early ignition. Start of hydrogen injection avoiding the piston end faces is helpful for combustion. Late hydrogen injection contributes to restraining the nitric oxides formations. Abstract: Opposed rotary piston (ORP) engines as a new type of internal combustion engines are free of connecting-rod mechanisms, have small engine size and mass. ORP engines have the abilities of delivering high power density. Hydrogen fuel applications in internal combustion engines contribute to nearly zero carbon emissions in the combustion processes. In this paper, the effect of hydrogen direct injection strategies and ignition timing on hydrogen diffusion, in-cylinder combustion, energy distributions, and nitric oxide (NO x ) emissions are investigated using a numerical simulation method regarding this novel internal combustion engine. The results showed that hydrogen was the most unevenly distributed in the combustion chambers for the start of injection (SoI) of −68.2° crank angle (CA) after top dead centre (aTDC) among the three hydrogen injection strategies; meantime, it presented the lowest combustion efficiency, being smaller than 98.5%. The peak in-cylinder pressure ranged from 40 bar to 83 bar for the given scenarios. The combustion durations were in the range of 20 °CA ~ 30 °CA for the ignition timing of −20.85 °CA aTDC ~ −11.06 °CA aTDC. The indicated thermal efficiency was higher than 38% over early ignition cases; the energy losses in total fuel energy by cylinder walls were lower than 15%. NO x emissions factors were lower than 36 g/kWh, and they were reduced by the retarded hydrogen injection. The engine performance and NO x emissions under early hydrogen injection scenarios are less sensitive to late ignition; additionally, the crank angle corresponding to the optimal efficiency was almost the same under different hydrogen injection strategies.